A systematic review on the social impact of green management in construction industry - Mingyi, Ying; Sai Hong, Tang; Supeni, Eris Elianddy; Yingqiao, Xia; Yujia, Ying (Human Resources Management Academic Research Society (HRMARS), 2024)
Green management in construction enterprises has gained prominence due to heightened environmental awareness and the need for sustainable development. This systematic review examines the social impact of green management practices within the construction industry, focusing on how these practices influence community well-being, employee satisfaction, and corporate reputation. By analyzing studies from 2000 to 2024, this review identifies key benefits, challenges, and gaps in the current literature, providing a comprehensive understanding of the social dimensions of green management. The findings highlight the importance of integrating social considerations into green management strategies to enhance their overall effectiveness and sustainability. This review offers valuable insights for researchers, construction firms, and policymakers aiming to foster socially responsible green practices in the construction sector.